PENGARUH ARUS TERHADAP KEKERASAN HASIL PENGELASAN BAJA ST 60 MENGGUNAKAN PENGELASAN SMAW - Ma'ruf Ma’ruf (Universitas Lambung Mangkurat, 2013)
The purpose of this study was to determine the effect of the current violence SMAW welds on weld metal, HAZ and base metal regions ST 60 steel using E6013 electrodes. This study uses eksprimental, hardness testing was conducted using the Rockwell B (HRB). Hardness testing with penetrator ball Ø 1/16